Diet and feeding of nestling Little Bitterns Ixobrychus minutus at fishponds: testing a new method for studying a difficult-to-monitor species. Issue 2 (3rd April 2018) - Flis, Adam; Gwiazda, Robert
ABSTRACT: Capsule: The diet and feeding of nestling Little Bitterns Ixobrychus minutus was studied using trail cameras. Little Bitterns nestlings were mostly provisioned with amphibians and small fish. They were fed in the morning and evening, but not during the night, and both parents provided similar amounts of food.